Seven faces : Brazilian poetry since modernism - Perrone, Charles A. (Book collections on Project MUSE., 1996)
"Study of Brazilian poetry from 1950-90 examines its 'seven faces' (a pun on Drummond's poem of the same name), phases, and trends. Introductory chapter reviews movement's initial phases and sets the stage for what follows: the legacy of the Modernist movement. Chapters 2-6 cover Concrete poetry and other vanguard groups, the lyricism of popular music, and different types of 1970s youth poetry. Also examines social and esthetic tensions in contemporary Brazilian poetry"--Handbook of Latin American Studies, v. 58.